2018
DOI: 10.1002/acn3.677
|View full text |Cite
|
Sign up to set email alerts
|

PI4K2A deficiency in an intellectual disability, epilepsy, myoclonus, akathisia syndrome

Abstract: We report a family of Saudi Arabian ancestry with two children presenting with global developmental delay, dystonia, disturbed sleep, and heat intolerance. By genome sequencing, we identified a nonsense variant in the first exon of PI4K2A that was homozygous in both affected individuals and was absent from, or heterozygous in, seven unaffected siblings. PI4K2A is highly expressed in the brain and a mouse model displays a neurological phenotype, implicating PI4K2A as a new disease gene for a neurological disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Based on the presentation in our patient, the patients described by Alkhater et al 17 and the previously characterised mice model we define a novel metabolic defect in the phosphatidylinositol pathway, presenting with a severe neurologic phenotype and expanding the existing phenotype with cutis laxa. Further work is needed to investigate how this might be relevant to the patient's clinical presentation.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Based on the presentation in our patient, the patients described by Alkhater et al 17 and the previously characterised mice model we define a novel metabolic defect in the phosphatidylinositol pathway, presenting with a severe neurologic phenotype and expanding the existing phenotype with cutis laxa. Further work is needed to investigate how this might be relevant to the patient's clinical presentation.…”
Section: Discussionmentioning
confidence: 76%
“…The male siblings described by Alkhater et al 17 presented with subtle facial dysmorphism at birth, but showed a normal development till the age of 5 to 6 months. From that age global developmental delay, dystonia, visual inattentiveness and loss of acquired skills were noted.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They shared a homozygous nonsense variant in P14K2A, a gene involved in membrane trafficking and neuronal survival. 23 Although the pathogenicity of this variant is plausible, it cannot be considered proven in the absence of either a second affected family or extensive functional analysis.…”
Section: Pi4k2amentioning
confidence: 99%